THE ROMANTIC IDEAL OF THE INDIVIDUAL AND ITS REFLECTION IN POSTCOLONIAL INDIAN ENGLISH POETRY - Rani, Monika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The current research paper explores the manifestation of the concept of the Romantic individual a person who believes in the primacy of emotions and imagination, in personal freedom and strong bond with nature in Indian English post-independence poetry. Being a trendy literary movement in Europe in the 18 th and 19 th centuries, romanticism assumed among other things a shift of interest towards the inner world of the individual, his emotions and his subjective experiences. This notion subsequently met other regions in the world, such as postcolonial nations like India. Since India got its independence out of the British rule, a number of poets began to write in English. These poets wrote a lot about themselves, their thoughts, emotions and experience and they discussed in poetry the identity, cultural shifts and liberty. This paper discusses the ways in which these poets envision Romantic values in their poem although they also touch upon such topics as the colonial past, contemporary life, and Indian culture. To know this the study considers the poems of popular Indian English poets like Kamala Das, Nissim Ezekiel, A.K. Ramanujan, and Jayanta Mahapatra. The poems are analysed with a view to identifying some common themes such as emotional expression, imagination, nature, rebellion and self discovery. Some simple statistics tools are also applied to back up the findings in the paper. The degree of the manifestation of these Romantic qualities in the chosen poems was measured according to a rating scale. The findings are clearly indicative that the Romantic ideal of individuality has a large contribution in the postcolonial Indian English poetic works. The personal voice and emotion are employed not merely as a means of self-expression but also as a means of social subversion by these poets, trying as they are to explore their identity within a shifting world. The paper brings out the union of Western Romanticism and the Indian cultural experiences in a distinct manner in Indian English poetry. This study allows the reader to realize the ways in which the concept of the individual stolen by Romanticism has been employed by Indian poets in order to describe their individual and national experiences. It also leaves the possibility of the future research in other forms of literature and other regional languages.